A more sensitive, efficient and ISO 17025 validated Magnetic Capture real time PCR method for the detection of archetypal Toxoplasma gondii strains in meat. Issue 13 (November 2017) - Gisbert Algaba, Ignacio; Geerts, Manon; Jennes, Malgorzata; Coucke, Wim; Opsteegh, Marieke; Cox, Eric; Dorny, Pierre; Dierick, Katelijne; De Craeye, Stéphane
Graphical abstract: Highlights: A molecular detection method for archetypal Toxoplasma gondii strains in meat is reported. This presents a more specific, sensitive and ethical method for the detection of T. gondii. ISO 17025 validated MC-qPCR (sensitivity MC-qPCR 94.12%; specificity: 100%) was completed. A full alternative for bioassay for the detection of T. gondii in various matrixes is described. All the experimental animals used during the study were re-used. Abstract: Toxoplasma gondii is a globally prevalent, zoonotic parasite of major importance to public health. Various indirect and direct methods can be used for the diagnosis of toxoplasmosis. Whereas serological tests are useful to prove contact with the parasite has occurred, the actual presence of the parasite in the tissues of a seropositive animal is not demonstrated. For this, a bioassay is still the reference method. As an alternative, various PCR methods have been developed, but due to the limited amount of sample that can be tested, combined with a low tissue cyst density, those have proved to be insufficiently sensitive. A major improvement of the sensitivity was achieved with magnetic capture-based DNA extraction. By combining the hybridization of specific, biotinylated probes with the capture of those probes with streptavidin-coated paramagnetic beads, T. gondii DNA can selectively be "fished out" from a large volume of meat lysate. Still, several studies showed an insufficient sensitivity compared with the mouse bioassay. Here we present a method that is more sensitive (99% limit of detection: 65.4 tachyzoites per 100 g of meat), economical and reliable (ISO 17025 validated) by adding a non-competitive PCR inhibition control (co-capture of cellular r18S) and making the release of the target DNA from the streptavidin-coated paramagnetic beads UV-dependent. The presented results demonstrate the potential of the modified Magnetic Capture real time PCR as a full alternative to the mouse bioassay for the screening of various types of tissues and meat, with the additional advantage of being quantitative.